Epstein-Barr Virus-Encoded Latent Membrane Protein 1 Upregulates Glucose Transporter 1 Transcription via the mTORC1/NF-κB Signaling Pathways - Zhang, Jun (J Virol, 2017)
Accumulating evidence indicates that oncogenic viral protein plays a crucial role in activating aerobic glycolysis during tumorigenesis, but the underlying mechanisms are largely undefined. Epstein-Barr virus (EBV)-encoded latent membrane protein 1 (LMP1) is a transmembrane protein with potent cell signaling properties and has tumorigenic transformation property. Activation of NF-κB is a major signaling pathway mediating many downstream transformation properties of LMP1. Here we report that activation of mTORC1 by LMP1 is a key modulator for activation of NF-κB signaling to mediate aerobic glycolysis. NF-κB activation is involved in the LMP1-induced upregulation of glucose transporter 1 (Glut-1) transcription and growth of nasopharyngeal carcinoma (NPC) cells. Blocking the activity of mTORC1 signaling effectively suppressed LMP1-induced NF-κB activation and Glut-1 transcription. Interfering NF-κB signaling had no effect on mTORC1 activity but effectively altered Glut-1 transcription. Luciferase promoter assay of Glut-1 also confirmed that the Glut-1 gene is a direct target gene of NF-κB signaling. Furthermore, we demonstrated that C-terminal activating region 2 (CTAR2) of LMP1 is the key domain involved in mTORC1 activation, mainly through IKKβ-mediated phosphorylation of TSC2 at Ser(939). Depletion of Glut-1 effectively led to suppression of aerobic glycolysis, inhibition of cell proliferation, colony formation, and attenuation of tumorigenic growth property of LMP1-expressing nasopharyngeal epithelial (NPE) cells. These findings suggest that targeting the signaling axis of mTORC1/NF-κB/Glut-1 represents a novel therapeutic target against NPC. IMPORTANCE Aerobic glycolysis is one of the hallmarks of cancer, including NPC. Recent studies suggest a role for LMP1 in mediating aerobic glycolysis. LMP1 expression is common in NPC. The delineation of essential signaling pathways induced by LMP1 in aerobic glycolysis contributes to the understanding of NPC pathogenesis. This study provides evidence that LMP1 upregulates Glut-1 transcription to control aerobic glycolysis and tumorigenic growth of NPC cells through mTORC1/NF-κB signaling. Our results reveal novel therapeutic targets against the mTORC1/NF-κB/Glut-1 signaling axis in the treatment of EBV-infected NPC.